Sleeping through COVID‐19: a longitudinal comparison of 2019 and 2020 infant auto‐videosomnography metrics. (19th August 2021) - Kahn, Michal; Gradisar, Michael
Abstract : Background: With the outbreak of the COVID‐19 pandemic, pediatric experts called attention to the potential adverse effects of living restrictions (e.g., lockdown) on child well‐being, but at the same time– acknowledged their possible benefits. To date, only few data‐driven reports have been published on child sleep during COVID‐19, and all have been based on parent‐ or self‐reports. This study used auto‐videosomnography to capture the effects of COVID‐19 stay‐at‐home orders imposed in the USA on objectively measured infant sleep. Methods: Auto‐videosomnography metrics of infants assessed nightly between January and May 2020 were compared with metrics of an equivalent infant cohort, assessed in the corresponding 2019 period. A total of 610 infants (50.7% girls) aged 6–18 months ( M = 11.8, SD = 3.6) were included, with 71, 472 analyzed nights. Multilevel models were applied to assess differences between 2019 and 2020 infant sleep pre‐ and during‐lockdown. Results: Whereas infant cohorts were equivalent in demographic and January–March/April sleep characteristics, during the 2020 lockdown infants had longer nighttime sleep durations ( M difference = 11.0 min, p = .01), later morning rise times ( M difference = 9.5 min, p = .008), and later out‐of‐crib times ( M difference = 12.3 min, p < .0001), compared to the equivalent 2019 period. In addition, weekday‐weekend differences in sleep onset and midpoint times were diminished during 2020 home‐confinement compared to the equivalent 2019 period (2019: M difference = 5.5 min, p < .0001; M difference = 4.5 min, p < .0001; 2020: M difference = 2.3 min, p = .01; M difference = 3.1 min, p < .0001, respectively). Conclusions: Notwithstanding the negative implications of COVID‐19 living restrictions in other domains, our findings indicate that there might be a silver lining—in promoting longer and more consistent infant sleep. These benefits should be considered in determining policy for the current and future pandemics.